2021
DOI: 10.1186/s12903-021-02033-w
|View full text |Cite
|
Sign up to set email alerts
|

Absorbance or organization into ankylosis: a microarray analysis of haemarthrosis in a sheep model of temporomandibular joint trauma

Abstract: Background Traumatic haemarthrosis was hypothesized to be the etiology of temporomandibular (TMJ) ankylosis. Here, taking haematoma absorbance as a control, we aimed to reveal the molecular mechanisms involved in haematoma organizing into ankylosis using transcriptome microarray profiles. Material/methods Disk removal was performed to building haematoma absorbance (HA) in one side of TMJ, while removal of disk and articular fibrous layers was perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Some genes that promote collagen matrix mineralisation, such as FMOD and LUM, reached peak expression during the cartilage formation phase , which is consistent with the findings of our previous study [ 17 ]. Furthermore, we found that the Wnt signaling pathway was significantly expressed at all time points in the TMJ ankylosis formation process (Table 1 and 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Some genes that promote collagen matrix mineralisation, such as FMOD and LUM, reached peak expression during the cartilage formation phase , which is consistent with the findings of our previous study [ 17 ]. Furthermore, we found that the Wnt signaling pathway was significantly expressed at all time points in the TMJ ankylosis formation process (Table 1 and 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we identified significant BP and pathways via genome-wide transcriptional analysis of the entire fibrous–chondral phase of traumatic TMJ ankylosis in a sheep model. Days 1, 4, 7, 9, 11, 14 and 28 were selected as time points based on the findings of previous studies [ 8 , 9 , 17 ] on the early stages of TMJ ankylosis include inflammation, hematoma organisation and TMJ fibrous-chondral ankylosis formation. The timeline was confirmed using serial histological sections and gene expression profiles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations